New Zealand Counter-Terrorism Strategy For Build Positive Peace To Support National Security - Shelvy Nujuliyani; Djayeng Tirto; Yulian Azhari; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This research is discusses the counter-terrorism strategies implemented by the New Zealand government following several terrorist attacks, including the Christchurch shooting (2019) and the Dunedin and Auckland stabbings (2021). Using Arthur Lyyke's strategy theory (2008), this study analyzes the means, ways, resources, and risk considerations inherent to effective counter-terrorism strategies. The study applies the counter-terrorism approach proposed by Jones & Libicki (2008), which divides counter-terrorism strategies into three categories: military deployment approach, police and intelligence approach, and policy approach. Through qualitative research with an analytical-descriptive approach, the study finds that the New Zealand government's counter-terrorism strategy comprises of two main approaches: the police and intelligence approach and the policy approach. The government's "no face no name" policy aims to deny terrorists any platform for recognition, while amendments to firearm possession laws and counter-terrorism legislation proposed by the prime minister facilitate the police's ability to restrict terrorist activities. These initiatives intend to foster positive peace and support national security.